Complying with the accessible information standard. (2nd May 2019) - Frankova, Helena
Abstract : Communication is an essential part of care, but not every resident will be able to understand or produce normal speech or writing. The Care Quality Commission will start to scrutinise communication plans; Helena Frankova explains how to comply.